Climate, Trade and Water: A "Grand Coalition"? - Patrick Messerlin (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
The paper argues first that the climate, trade and water communities should leave aside their prejudices, and it provides clear evidence that the three communities confront the same vested interests when trying to solve their common problem of free riding. Then, it argues that such strong similarities speak in favour of "sister" world regimes in these three domains. These sister regimes should first share the key principles of non-discrimination (national treatment and most favored nation) embodied in the WTO. Second, by contrast, the climate and water communities should review the other WTO rules in order to adapt them to their specific demands when needed. Interestingly, when doing so, these two communities may provide much needed inspiration for improving some rules of the current trade regime. Finally, the climate and water regimes may also adopt provisions on pricing that are not needed by the trade regime which deals mostly with well functioning markets.
Keywords: F13; F18; F5; Q4; Q56; Q58; 330